1985
DOI: 10.1210/jcem-60-1-164
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Analysis for the Evaluation of the Circadian Rhythms of Plasma Cortisol, Androstenedione, and Testosterone in Normal Men and the Possible Influence of Meals

Abstract: To evaluate the circadian rhythms of plasma androstenedione (delta) and testosterone (T), we used continuous blood withdrawal at 30-min intervals for 24 h to obtain integrated concentrations in six normal men. The data were submitted to contrast analysis as well as to a graphical method with smoothing of the variations between samples. As reference, cortisol (F) levels also were measured, since they have a well defined circadian rhythm. Integrated F concentrations had a circadian rhythm, with the highest level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 10 publications
2
16
0
1
Order By: Relevance
“…Recent careful studies of the periodicity of ACTH secretion have demonstrated a rise in ACTH around mealtimes that is superimposed on the well-established diurnal pattern of hormone secretion. 20 Synchronous changes of aldosterone and cortisol strongly support the suggestion that ACTH is the principal regulator of aldosterone secretion in this condition. 4 - 21 Since plasma aldosterone, but not cortisol or corticosterone, levels are elevated in these patients, the abnormality appears to concern an aspect of adrenocortical function other than the pituitary-(ACTH) adrenal (cortisol) axis.…”
Section: Figure 5 Relationship Between Plasma Concentrations Of Angimentioning
confidence: 66%
“…Recent careful studies of the periodicity of ACTH secretion have demonstrated a rise in ACTH around mealtimes that is superimposed on the well-established diurnal pattern of hormone secretion. 20 Synchronous changes of aldosterone and cortisol strongly support the suggestion that ACTH is the principal regulator of aldosterone secretion in this condition. 4 - 21 Since plasma aldosterone, but not cortisol or corticosterone, levels are elevated in these patients, the abnormality appears to concern an aspect of adrenocortical function other than the pituitary-(ACTH) adrenal (cortisol) axis.…”
Section: Figure 5 Relationship Between Plasma Concentrations Of Angimentioning
confidence: 66%
“…Because about 70% of androstenedione is derived from adrenals, the pattern of androstenedione was similar to that of cortisol, even in the nocturnal lifestyle group, which was also supported by a previous study. 16) In the nocturnal lifestyle group, the cortisol concentration increased markedly at 21:00, possibly caused by some anxious anticipation of the subsequent nocturnal life and the continuous intake at night. On the other hand, the increase in cortisol concentration may be responsible for the decrease of free testosterone in the nocturnal lifestyle group by competing with testosterone for an SHBG binding site.…”
Section: Discussionmentioning
confidence: 94%
“…Testosterone (including testosterone and free testosterone), DHT and androstenedione are important androgens. Cortisol has a well definded circadian rhythm [15][16][17][18][19] and is related to androstenedione, which is produced by both the adrenals and testes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of a large peak of plasma cortisol coinciding with the noon meal and a smaller peak after the evening meal gives evidence for the influence of meal timing on the daily plasma cortisol pattern (138)(139)(140). The mechanism by which ingestion of food stimulates cortisol secretion is unknown.…”
Section: Diurnal Rhythms Of the Hypothalamicpituitary-adrenal Axis Anmentioning
confidence: 99%